P692 Positive histological margins is a risk factor of recurrence after ileocaecal resection in Crohn's disease. (25th January 2019) - Riault, C; Diouf, M; Chatelain, D; Le Mouel, J p; Loreau, J; Turpin, J; Yzet, C; Brazier, F; Sabbagh, C; Dupas, J l; Nguyen-Khac, E; Fumery, M
Abstract: Background: Surgical resection is not curative in Crohn's disease (CD) and recurrence after surgery is a common situation. The identification of patients at high risk of recurrence remains disappointing in clinical practice. The impact of residual microscopic disease on margins on the risk of recurrence after ileocaecal resection is still subject to debate. Methods: All patients who underwent ileocaecal resection between January 1982 and December 2016 were prospectively identified. Demographic data, clinical, surgical and histological variables were retrospectively collected. Positive histological margin was defined by the presence of acute inflammatory lesions on margins: erosion, ulceration, chorion infiltration by neutrophils poly- nuclears, cryptic abscesses or cryptitis. Results: 125 patients were included, with a median follow-up of 8 years (Interquartile Range (IQR), 4.3–15.2). Half (49.6%, n = 62) were women, and the median age at surgery was 33 years (24–42). Fifty-six (44.8%) had positive inflammatory margins. Five years after surgery, , respectively, 29 (51%) and 23 (34%) patients with positive and negative margins had clinical recurrence ( p = 0.034). At the end of the follow-up, respectively, 60% ( n = 34) and 47% ( n = 33) patients had clinical recurrence ( p = 0.07). CD-related hospitalisations were observed in, respectively, 37.5% ( n = 21) and 18.8% ( n = 13) with positive and negative margins ( p = 0.02). Fourteen patients (25%) with positive intestinal margins were reoperated at the end of the follow-up compared with 5 patients (7%) with negative margins ( p = 0.04). Multi-variate analysis confirmed that positive intestinal margin was independently associated with CD-related hospitalisation (Odds Ratio (OR), 2.5 (CI 95%, 1.1–5.5), p = 0.03) and surgical recurrence (OR, 4 (95% CI, 1.3–12.5), p = 0.01). Conclusions: Positive histological margin, as defined by the presence of erosion, ulceration, chorion infiltration by neutrophils polynuclears, cryptic abscesses or cryptitis, was associated with an increased risk of clinical and surgical recurrence after ileocaecal resection for Crohn's disease.